The Peruvian Government Fight Against Child Labour and Trafficking of Children and Teens: Progress and Challenges - Vega Luna, Eduardo (2015)
By 2011 the child population was 36% concentrating the highest rates of poverty and working was one million seven hundred ninety five thousand, of which 33,9% risk undertaking work over 36 hours a week and despite the Peruvian state initiatives is still much to do.